On-water magnetic NiFe2O4 nanoparticle-catalyzed Michael additions of active methylene compounds, aromatic/aliphatic amines, alcohols and thiols to conjugated alkenes. Issue 98 (7th October 2016) - Payra, Soumen; Saha, Arijit; Banerjee, Subhash
Abstract : Here, we have demonstrated Michael addition of active methylene compounds, aromatic/aliphatic amines, thiols and alcohols to conjugated alkenes using magnetic nano-NiFe2 O4 as reusable catalyst in water. Abstract : Here, we have demonstrated the Michael addition of active methylene compounds, aromatic/aliphatic amines, thiols and alcohols to conjugated alkenes using magnetic nano-NiFe2 O4 as reusable catalyst in water. Nano-NiFe2 O4 efficiently catalyzed the formation of C–C and C–X (X = N, S, O etc. ) bond through 1, 4-addition reactions.